Semiconductor-laser-based hybrid chaos source and its application in secure key distribution - Zhao, Zexi (2021)
An analog-digital hybrid optical chaos source and a corresponding secure key distribution (SKD) scheme are proposed. An analog-digital hybrid electro-optic feedback loop is introduced to enhance the robustness of the chaotic semiconductor lasers. The source, which can adopt robust digital synchronization strategies, could generate a broadband analog optical chaotic signal of high dynamical complexity. Furthermore, the source reduces the requirement on the processing speed of digital components and simplifies the hybrid system structure markedly. For demonstrating, we build a SKD system with the proposed chaos source. Since this SKD scheme is compatible with digital optical networks, the commercially available communication techniques can help to make it insensitive to impairments in fiber optic links. This feature has potential in long-haul SKD.